How Semantically Labeled Scent-Gender Associations Influence the Evaluations of Scent and Texture - Iseki, Sayo; Motoki, Kosuke; Sakata, Ryosuke; Kitagami, Shinji (Frontiers in Psychology, 2021)
Sensory evaluation can be influenced by semantic information such as gender descriptions. Gender categories are associated with tactile information (e.g., female = soft/smooth, while male = hard/rough). Feminine scents (e.g., floral) are typically perceived as soft and smooth. Thus, semantic labels of gender (feminine/masculine qualities) may influence congruent sensory evaluation (i.e., female = soft/smooth, male = hard/rough). This study examined how semantically labeled scent-gender associations influence the evaluation of scent and texture. Specifically, we examined whether “feminine” and “masculine” labels applied to neutral scents that have not been associated with gender influence scent and haptic evaluation. Participants sniffed a feminine-labeled or masculine-labeled scent embedded on soft and rough papers. They then evaluated the scent (e.g., gender perception) and texture (e.g., hedonic evaluation). The results demonstrated that participants who sniffed a feminine-labeled (vs. masculine-labeled) scent perceived it as more feminine. However, contrary to our expectations, gender labeling of scent did not influence haptic evaluation. These findings indicate that semantic labeling of scents (i.e., feminine/masculine) may alter the gender perception of a scent but not the tactile evaluation. Practical implications for (online) sensory marketing are discussed.